Pengembangan Desain Pembelajaran dengan Model Assure pada Pembelajaran Tematik Terpadu di Sekolah Dasar - Leli Tuti Suharni (Jurnal Basicedu, 2019)
His study aims to produce ASSURE model of learning design on integrated thematic learning theme 2 grade V Elementary School that is valid, practical, and effective. Learning design developed in the form of RPP (Learning Implementation Plan). This type of research is development research with the ASSURE model. The research subjects were Grade V students of SD Negeri 09 Ulakan Tapakis. Data was collected using observations sheet of the implementation of learning design, student response questionnaire, educator response questionnaire, student activities during the learning process and learning outcomes. The data obtained are then processed and analyzed descriptively. It is expected that the results of the study indicate that the learning design developed is in the very valid category. Based on the results of the trials that will be conducted, it is found that the learning design is expected to meet practical aspects in terms of the response of educators and students. This learning design is also expected to meet the effectiveness aspects seen from: 1) learners' activities; 2) attitude; 3) students' knowledge that is expected to exceed KKM; 4) student skills. The learning design developed in the form of lesson plans has the following characteristics: 1) practical in use and 2) using clear, logical, and systematic language.